Avaliação de pacientes masculinos submetidos à biópsias de mama, exames ecográficos, anatomopatológicos e citopatológicos em um hospital universitário federal do Rio Grande do Sul - Souza, Laís Praetzel Soeiro de (2023)
Male breast cancer is a rare disease, with a low frequency in the general population. This type of cancer represents about 0.2% of all cancers in men, accounting for 0.1% of cancer deaths in men. Despite the rarity of this comorbidity, there is an increase in the incidence of this pathology, mainly in the southern region of Brazil. Due to the rarity of this pathology, an etiology is still not fully known. This study evaluated the presence of breast lesions in men through ultrasound, pathological and cytological examinations performed in men at the University Hospital of Santa Maria/RS. The study had a retrospective, quantitative and cross-sectional approach, considering data from the period from 2004 to 2019. The study group consisted of 27 male patients, with a mean age of 52.2±13.09 years, with one individual he was. excluded A total of 1,974 reports were evaluated, among men and women, with the presence of 594 breast cancers in women and 2 in men being observed. Regarding the biopsy, 31% of the individuals (n=8) presented a positive report (with alterations), 54% (n=14) presented a negative report (no alterations) and in 15% (n=4) the result was not found. /biopsy report. Due to the rarity of the pathology, an extensive period of 15 years was analyzed to find a study sample. From this sample it was possible to evaluate the characteristics of the lesions, their prevalence, ecological characteristics, among other aspects. There is a need to implement public policies associated with men's health, which address male breast cancer, from a popular perspective, within the scope of primary care, in health promotion policies.